ENTREPRENURSING IN THE EYES OF NURSING STUDENTS: SEBUAH STUDI FENOMENOLOGI HERMENEUTIKA - Anthony Stafford Pangemanan; Grace Fresania Kaparang; Frendy Fernando Pitoy; Nova Lina Langingi (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
Current and predicted economic perplexities, high unemployment rate, and difficulties of obtaining and extending of licensure should open the eyes of nursing students not to sojourn in the stereotype nurses’ mindset as employees of health care institutions only, but also to look at the option of entreprenursing. This study aims to investigate how nursing students see entreprenursing concept and give meaning to it. The research design used was hermeneutic phenomenology with Heidegger's philosophical underpinning, Van Manen's thematic analysis technique and the trustworthiness of the data ascertained. The results of the thematic analysis of hermeneutics witness the results of data saturation on the response of 9 participants. Two meanings of entreprenursing emerged from nursing students’ perspective. Independent entreprenurses are